2011
DOI: 10.1016/j.meegid.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Using phylogeography to characterize the origins of the HIV-1 subtype F epidemic in Romania

Abstract: Background During the late 1980s and early 1990s, an estimated 10,000 Romanian children were infected with HIV-1 subtype F nosocomially through contaminated needles and blood transfusions. However, the geographic source and origins of this epidemic remain unclear. Methods Here we used phylogenetic inference and “relaxed” molecular clock dating analysis to further characterize the Romanian HIV-1 subtype F epidemic. Results These analyses revealed a major lineage of Romanian HIV sequences consisting nearly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 23 publications
5
39
0
Order By: Relevance
“…The T MRCA of subtype G clade here estimated (1968: 1956–1976) is also fully consistent to that previously estimated for this subtype (1970: 1960–1978) [58]. This onset date is comparable to that estimated for subtype F (1967: 1956–1976) [59]; but more recent than that of subtypes A1 (1954: 1940–1968), C (1955: 1934–1972), and D (1947: 1938–1955) [58].…”
Section: Discussionsupporting
confidence: 90%
“…The T MRCA of subtype G clade here estimated (1968: 1956–1976) is also fully consistent to that previously estimated for this subtype (1970: 1960–1978) [58]. This onset date is comparable to that estimated for subtype F (1967: 1956–1976) [59]; but more recent than that of subtypes A1 (1954: 1940–1968), C (1955: 1934–1972), and D (1947: 1938–1955) [58].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the overall low prevalence of the CRFs_cpx lineages carrying fragments of those ancient may reflect a later emergence of these variants when compared to more prevalent HIV-1 subtypes and CRFs. The evolutionary analyses performed here, however, support that complex CRFs probably started to circulate in Central Africa between the late 1950s and the late 1960s, which coincides with the estimated onset date of several prevalent HIV-1 group M clades including: subtype A1 (T MRCA  ~ 1955) [41], subtype C (T MRCA  ~ 1955–1965) [41, 50, 51], subtype F1 (T MRCA  ~ 1960–1970) [52, 53], subtype G (T MRCA  ~ 1965–1970) [41, 54], the CRF01_AE (T MRCA  ~ 1970–1975) [41, 55, 56], and the CRF02_AG (T MRCA  ~ 1965–1975) [41, 57, 58]. The estimated T MRCA also overlaps with a period of demographic transition of the HIV-1 group M in the DRC around 1960 (95% HPD: 1952–1968), from an early phase of relatively slow exponential growth to a second phase of faster exponential growth [2].…”
Section: Discussionsupporting
confidence: 52%
“…Ten of the 49 HIV participants had previous HIV clade evaluation (due to virological failure); all had F1 HIV subtype. Furthermore, previous molecular demographic and phylogeographic analyses (Mehta et al 2011; Mbisa et al 2012) demonstrated that F subtype was responsible for the Romanian nosocomial pediatric HIV epidemic. Participants were excluded if they were unable to provide informed consent, had a neurocognitive morbidity unrelated to HIV condition (e.g., recent and/or significant traumatic brain injury, color blindness, hearing deficit that appears to affect auditory comprehension, neurosyphilis, stroke, etc.…”
Section: Methodsmentioning
confidence: 90%